PROGRAM PEMBELAJARAN SOSIAL EMOSIONAL âAKU ANAK BAIKâ UNTUK MENURUNKAN PERILAKU AGRESIF PADA SISWA TAMAN KANAK-KANAK - , Rika Vira Zwagery ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Aggressive behavior needs to be treated earlier because itâs have negative impact on the lives of children in the future. For this reason, certain interventions to reduce aggressive behaviours in schools are needed. âAku Anak Baikâ is a program intended to decrease studentsâ aggressive behaviours. âAku Anak Baikâ is a program based on social emotional learning refers to "Strong Start" program made by Merrell, Whitcomb & Parisi (2009). This study aims to tests the module "Aku Anak Baik" for students who behave aggressively. It hypothesized that âAku Anak Baikâ would be useful to reduce aggressive behaviours. This study used A-B-A design. Lembar Pencatatan Perilaku Agresif (Aggressive behaviour record sheets) were used as a measurement tool. After the data were analyzed visually and using Wilcoxon Signed Rank Test, it is known that âAku Anak Baikâ can reduce the aggressive behaviours of kindergarten students.